2018
DOI: 10.1080/14786419.2018.1477146
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of dental biofilm with a tincture of Bauhinia forficata leaves: an ex-vivo study

Abstract: The inhibitory activity of a Bauhinia forficata tincture (TBF) was investigated against oral microorganism's strains and against a mature oral biofilm. The viability of planktonic cells was analyzed by Minimal Inhibitory and Microbicidal concentrations of TBF. Salivary samples from health volunteers were collected and mixed to form a saliva pool. An aliquot from this pool were seeded on membranes, which were incubated to form biofilm (48 h). The biofilm was treated according to the groups: G1-Chlorhexidine 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…Bauhinia forficata tincture Phenol, flavonoids, acid derivatives [90] Berberis goudotii Tannin, polyphenol [76] Stem-leaf American ginseng Saponin Terpenes impede the peptidation of the expanding peptidoglycan chain and cell wall production enzymes. [100] [91]…”
Section: Oxapampa Propolis Flavonoidsmentioning
confidence: 99%
“…Bauhinia forficata tincture Phenol, flavonoids, acid derivatives [90] Berberis goudotii Tannin, polyphenol [76] Stem-leaf American ginseng Saponin Terpenes impede the peptidation of the expanding peptidoglycan chain and cell wall production enzymes. [100] [91]…”
Section: Oxapampa Propolis Flavonoidsmentioning
confidence: 99%
“…Thus, B. forficata extract could be potentially used—together with norfloxacin—to treat infections caused by multidrug-resistant S. aureus [ 73 ]. Ferreira-Filho et al [ 71 , 72 ] showed antimicrobial effects of B. forficata leaf tincture (20% in a 70% hydroethanolic solution) against oral microorganism strains and mature dental biofilms obtained from salivary samples and formed on membranes or bovine enamel blocks. The tincture is a promising preventive agent of dental caries, with no cytotoxic effect, tested against oral fibroblast cells.…”
Section: Biological Activitymentioning
confidence: 99%
“…Toxic effects were not reported in most methodological approaches (e.g., [ 72 , 76 , 84 , 89 , 97 , 138 , 141 , 173 ]), however some research findings deserve attention. It has been reported that acute treatment with B. forficata crude extract (2.85 g/kg) injected intraperitoneally caused the death of 50% of the animals, yet oral administration (0.5 to 5.0 g/kg) is not toxic [ 1 ].…”
Section: Biological Activitymentioning
confidence: 99%
“…(Adewole, Caxton Martins & Ojewole, 2007;Ferreres et al, 2012;Jorge et al, 2004;Kim et al, 2011;Meneses et al, 2007;Pinheiro et al, 2006;Salgueiro et al, 2013;Sousa et al, 2004;Tzeng et al, 2009;Yamasaki et al, 2011;Zanatta et al, 2008). (Ferreira Filho et al, 2018). Outros autores acharam a atividade antibacteriana em B. forficata e B. variegata fraca ou nula (Silva & Cechinel Filho, 2002;Martinez et al, 2011).…”
Section: Papel De Antioxidantesunclassified